EVALUATING THE IMPACT OF TOFACITINIB IN A PATIENT WITH DOWN SYNDROME AND ALOPECIA AREATA: A CASE STUDY - Dr. Manisha Mishra; Dr. Parneet Kaur; Dr. Shalabh Singla (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Alopecia Areata (AA) has become an increasingly prevalent category of autoimmune illness wherein patients present with one or multiple areas of hair loss that are not scarring in nature and are linked to variations in immune function. Treating alopecia areata in patients with chromosomal abnormalities such as Down syndrome can prove to be extremely challenging. It thus becomes relevant to present a clinical case report of a 30-year-old male with Down’s syndrome who was severely affected by alopecia areata which compromised his ability to function effectively. Although the patient has a genetic predisposition that limits previous treatments, standard methods to treat AA have failed in the subject. However, Tofacitinib, an oral Janus kinase (JAK) inhibitor, has increased popularity as a therapeutic option by virtue of its modulating effects on the immune system. The patient experienced significant regrowth of hair during the three-month follow up resulting in beautiful coverage and density of hair on the scalp. The studies indicate minimal to negative significant adverse effects, suggesting that tofacitinib had a favorable safety profile in treating alopecia areata in patients with Down syndrome. This emphasizes the necessity of individualized treatment for people with autoimmune disorders. These trials necessitate comprehensive further clinical investigations focusing on the safety, long-term hazards, and efficacy of tofacitinib in this patient demographic.